Efektivitas Aplikasi Sistem Informasi Manajemen Baznas (Simba) Dalam Pengelolaan Dana Zakat Di Baznas Provinsi Sumatera Selatan (Studi Kasus Baznas Provinsi Sumatera Selatan) - Ica Aprianti Dwi Putri; Syamsiar Zahrani; Hilda (CV. ITTC INDONESIA, 2024)
Zakat is a pillar of Islam which is legally required, the command of zakat is also contained in the Qur'an and Hadith. If the wealth is sufficient to meet the nishab and haul, then it is obligatory to pay zakat mal. This study aims to find out in depth about the Baznas Management Information System (SIMBA) application in the management of zakat funds in Baznas, South Sumatra Province. The problems that will be discussed in this study are: (1) How is the process of managing zakat funds on the Application (SIMBA) in the Baznas of Sumatra Province. (2) How is the effectiveness of zakat fund management before and after using the Application (SIMBA) for BAZNAS of South The research objectives (1) are to determine the effectiveness of zakat fund management after and before using the Baznas Management Information System (SIMBA) application for BAZNAS, South Sumatra Province. (2) To identify and identify the factors supporting and inhibiting effectiveness in managing zakat funds through the Baznas Management Information System (SIMBA) application at BAZNAS, South Sumatra Province. The results of this study (1) The Baznas Management Information System (SIMBA) application has been running well, and has greatly helped the Baznas of South Sumatra Province in managing the data of Muzaki and Mustahik as well as incoming and outgoing zakat funds, so that it is more efficient and effective in its management. (2) Previously, BAZNAS still used the manual method, which made staff a little overwhelmed, but since BAZNAS, South Sumatra Province, using the Baznas Management Information System (SIMBA) application, it has made it easier for staff in managing data and zakat funds for Mustahiq. The first conclusion, the supporting factor in the use of the Baznas Management Information System (SIMBA) application is the support from the leadership of BAZNAS South Sumatra Province and information technology infrastructure. Second, assisting the collection and finance department in the management of zakat funds from the payment process, management and distribution to the Mustahiq.